“It works for us”: the dynamics of influence and intimacy within couples - Chen, Wen-Chi (Kansas State University, 2011)
The goals of this study were to investigate the definitions of influence and closeness from the perspectives of the couples, the techniques or approaches couples use to share influence and maintain closeness in their relationships, the themes associated with different relating styles, ways couples handle discrepancies and incompatibilities, and the relationship issues associated with specific relating styles. Eight married couples residing in northeast Kansas were interviewed for this study. The participants were selected through a screening survey distributed to a university student body to collect basic demographics and couple relating styles. The eight couples were chosen because the relating styles they reported were diverse enough to provide the needed maximum variation and a general representation of the sample pool. A style of relating model – couple map was created to help couples visualize how they relate to their partners in terms of influence and closeness. This study begins to fill the gap in the research by creating an integrated model to understand couple relational patterns and by giving voice to couples and allowing them to share their experiences on how they share influence and maintain closeness in their relationships. Through the lens of Symbolic Interaction Theory and Social Exchange Theory, this study sheds light on the cognitive and behavioral strategies couples use to relate to each other while striving to meet personal and mutual needs for influence and closeness in their marriages.
Keywords: Closeness; Influence; Relating styles; Marriage; Couple; Qualitative; Counseling Psychology (0603); Gender Studies (0733)